Epidemiological Parameters of Dengue Infections in Pakistan - Najab Gul, Sehrish Gul, Gul Mayada Anwar, Muhammad Ali, Mehrosh Gul, Ehsan Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim of this research work was to find out epidemiological features associated to age, nature of prevalence, serology and severity of the disease. Methodology: This study was conducted in Benazir Bhutto Hospital; Rawalpindi and the duration of this study was from June 2021 to November 2021. We collected total 149 specimens of sera of the suspected patients appearing with the symptoms of dengue. We analyzed the gathered samples with the help of serological detection of IgM (Immunoglobulin-M), IgG (Immunoglobulin-G), RT-PCR (Reverse transcriptase-Polymerase chain reaction) and culture of virus in CelllineC36/36. Results: Findings of this research work showed that out of total one hundred and forty-nine specimens, 32.20% (n: 48) were identified with dengue virus with the use of RT-PCR & cell culture and 72.50% (n: 108) samples were found positive by serology. Of one hundred and eight cases, 26.80% (n: 48) patients were IgM positive, 41.0% (n: 61) were both IgM & IgG positive and 4.70% (n: 07) patients were IgG positive only. There was very high prevalence of dengue in age-group of patients having 20-29 years of age and the incidence of the infection was much high in male patients as compared to females. There was highest epidemic intensity in month of June as compared to other months. Practical Implication: This current research makes it possible to classify the serological results of dengue by mixed primary-secondary, primary and secondary dengue infections. There is also relation of dengue infection with the season as there is high activity of this infection after season of monsoon Conclusion: The prevalence of dengue is very endemic in our country Pakistan and the most vulnerable age group was 20-29 years for this infection. There is strong need of the effective prevention as well as control measures for the reduction of this infection. Keywords: Infection, serology, dengue, RT-PCR, IgM, epidemiology, IgG, prevention, prevalence, incidence, endemic.